Retina - Ryan, Stephen J., 1940-2013 (Saunders, 2013)
Unequalled in scope, depth, and clinical precision, Retina, 5th Edition keeps you at the forefront of today's new technologies, surgical approaches, and diagnostic and therapeutic options for retinal diseases and disorders. Comprehensively updated to reflect everything you need to know regarding retinal diagnosis, treatment, development, structure, function, and pathophysiology, this monumental ophthalmology reference work equips you with expert answers to virtually any question you may face in practice. Benefit from the extensive knowledge and experience of esteemed editor Dr. Stephen Ryan, five expert co-editors, and a truly global perspective from 358 other world authorities across Europe, Asia, Australasia the Americas. Examine and evaluate the newest diagnostic technologies and approaches that are changing the management of retinal disease, including future technologies which will soon become the standard. Put the very latest scientific and genetic discoveries, diagnostic imaging methods, drug therapies, treatment recommendations, and surgical techniques to work in your practice.